PERILAKU PENGGUNAAN MEDIA SOSIAL DAN IDENTITAS DIRI SETELAH PANDEMI COVID 19 - FANNY HENDRO ARYO PUTRO; RIRIN NOFITA; AYU PUSPITASARI (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2023)
Research on the behavior of using social media and self-identity after the Covid 19 pandemic was motivated by the phenomenon of covid 19 and the behavior of young people who are very active in social media in their daily life, social media has become a routine that cannot be missed. So, with this phenomenon, researchers want to know the behavior of using social media in accessing social networks, forms of interaction or implications of using social media. researchers used a qualitative approach with audience ethnography methods (audience ethnography). When collecting data, the techniques used were direct observation and in-depth interviews. in this study shows that the relationship or relationship that is created is a social achievement or assessment of a community or forum so that Instagram as a social media as a medium for expanding self-interest or existence by making statuses, in presenting various content and commenting and commenting is a form of fostering relationships other than that as the development of the concept of self-identity for the sake of expression, narcissism and pleasure. As well as interacting with the outside world, to meet the growing information needs in the form of content. It can be said that Instagram is a place for self-existence among undergraduate students of the Communication Department at Boyolali Universit